ZERO EXEMPTION THRESHOLD FOR CORPORATION AS AN ALTERNATIVE TO INCREASE VAT REVENUE - Muhammad Haidar Taqiyyuddiin; Suparna Wijaya (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The registration threshold for which enterprises are exempt from the obligation to be registered as taxable enterprises (Exemption Threshold) in Indonesia’s Value Added Tax (VAT) regime is exceptionally high compared to most of other countries. This situation resulted in the potency of VAT revenue that isn’t collected by Indonesian government at the optimal level, which is why the Indonesia’s Exemption Threshold needs to be reconsidered. This research explores the possibilities to regulate Exemption Threshold through a new concept, that is the zero Exemption Threshold for corporation. This study’s research design is multi-method qualitative study, using primary and secondary qualitative data for analysis. The results provide that the concept of zero Exemption Threshold for corporation is not only followed by arguments that give justification for this concept, but also followed by arguments that give refusal for this concept. In regards to VAT revenue, that concept can bring more VAT revenue, but the increase is not significant. Furthermore, that concept can be enforced by Indonesia’s Ministry of Finance after considering several crucial points. Lastly, the idea of zero Exemption Threshold for corporation can bring positive and negative impacts for Indonesia in general. The merits from this research are to accommodate a fresh insight in rearranging Exemption Threshold in order to optimalize VAT revenue, to be an input and consideration material for the Indonesia’s Ministry of Finance in the context of rearranging Exemption Threshold, and to contribute to the literature related to the topic discussed in this research. Nevertheless, this research also has its own flaw, namely this research uses qualitative method so that the research results are more subjective. To cover this flaw, it is necessary to conduct further research with quantitative method to produce more objective research, as well as to complement and strengthen this research.